IMPLEMENTASI METODE SAW TERHADAP PEMILIHAN KARYAWAN TERBAIK - Rimmar Siringoringo; Romindo Romindo; Rudolfo Rizki Damanik (Journal Information System Development (ISD), 2023)
The best and qualified employees will make the company increase in its operations and can grow rapidly. But the constraints that exist in the CV. Maju Jaya Award for the best employee is still not optimal in its implementation. Therefore we need a system that can assist companies in evaluating the best employees optimally. Decision making to determine the best employee can be done by the company by assessing the performance that has been carried out by its employees at CV. Maju Jaya is influenced by several criteria, namely Knowledge, Discipline, Responsibility, Attendance, Teamwork. This decision support system uses the Simple Additive Weighting (SAW) method where the decision-making process can be calculated based on the calculation of the weight of each criterion, so that the best employees in the company can be selected quickly.